(untitled) (Research, Society and Development, 2019)
Tomato production as well as its commercialization plays an important role in the economy of the state of Goiás. In 2017 the state of Goiás occupied the first place in the national ranking of tomato production with 1,298,088 tons. The objective of this paper is to present the origin of tomatoes marketed in CEASA - Goiás, and the quantity supplied by the microregions of the state of Goiás, as well as the total quantity in tons sold in this supply center by each state of Brazil, knowing that the state of Goiás is one of the largest suppliers. The data collected at CEASA - GO, made available by the Technical Division, are the result of the institution ’s own collection and calculation methodologies. The clipping presented is from 2017 to 2018, of the varieties longa vida and saladete. Data processing was supported by ArcMap Desktop Software, from ESRI’s ArcGIS package. It was found that the tomatoes come from several states, however, the predominance is from the state of Goiás. Given the results, it can not be concluded that the state of Goiás is the largest producer, but it can be concluded that it is the largest tomato supplier for CEASA - Goiás.